2017
DOI: 10.17116/hirurgia20171258-65
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional knotless barbed sutures during primary total knee arthroplasty: effective solution or new problem?

Abstract: The use of bidirectional knotless barbed sutures in TKA reduces the time of surgery, does not affect the volume of hidden blood loss or PPI occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Finally, we identified 1,472 TKAs (1,270 patients) assessed in 12 RCTs. 1,4,[17][18][19][20][21][22][23][24][25]29 The detailed baseline characteristics and general intervention information are presented in ►Table 1. All the articles were published in English, Chinese, and Russian between the years 2012 and August 2019.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we identified 1,472 TKAs (1,270 patients) assessed in 12 RCTs. 1,4,[17][18][19][20][21][22][23][24][25]29 The detailed baseline characteristics and general intervention information are presented in ►Table 1. All the articles were published in English, Chinese, and Russian between the years 2012 and August 2019.…”
Section: Search Resultsmentioning
confidence: 99%
“…Some studies evaluating wound closures using KBS and KTS techniques have supported no increase in wound-related complications with KBS. 1,4,[17][18][19][20][21][22][23][24][25] However, other authors have suggested an increased rate of complications. [14][15][16] Campbell et al 14 found that wound close with KBS showed a higher rate of infection and overall closure-related complications and they thought doctors should avoid using barbed suture for superficial closure after knee arthroplasty.…”
Section: Pooled Analysis Of Knee Range Of Movements (6 Weeks) Between Kbs and Ktsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zaruby et al argue that barbed suture are strong and safe 32 . Chugaev et al argue that barbed suture are less time‐consuming and safer than traditional suture 33 . These are all points in favour of barbed suture.…”
Section: Discussionmentioning
confidence: 99%
“…Zaruby et al [ 23 ] augured that bidirectional barbed suture was safe and effective, and its strength and surrounding tissue reactions were comparable to those of absorbable suture. Chugaev et al [ 24 ] indicated that closure of joint capsule and subcutaneous adipose tissue with bidirectional knotless barbed sutures in primary TKA was safe and time-saving, because it did not cause occult blood loss or the occurrence of infection. Shermak et al [ 25 ] found barbed sutures were associated with greater difficulty in the healing of the knee extensor mechanism and higher complication rates when fascia and subcutaneous tissues were sutured.…”
Section: Discussionmentioning
confidence: 99%